Coral reef-associated bryozoans of Jamaica - Winston, J. E.; Jackson, J. B. (Zootaxa, 2021)
As part of a long-term ecological study of the cryptic comunity of Jamaican coral reefs carried out by Jeremy B.C. Jackson and associates during the 1970s and early 1980s, collections were made of reef bryozoans found at 14 sites around the island. Space occupied by bryozoans on undercoral surfaces is dominated by relatively few species. However, during scanning electrone microscopy study and monograph preparation a diverse assortment of relatively rare species was discovered. Of the 132 species found, 56%, 74 species (70 cheilostomes and 4 cyclostomes) are new, as are one family (Inversiscaphidae) and 5 genera (Planospinella, Caribaria, Spirocoleopora, Gemellitheca, and Palliocella).